2022
DOI: 10.1128/spectrum.03488-22
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Negatively Regulates Intracellular Bacterial Killing by Pyroptosis in Burkholderia pseudomallei - Infected Mouse Macrophage Cell Line (Raw264.7)

Abstract: Surface TLRs have been well established to play an essential role in Burkholderia pseudomallei infection. However, the role of endosomal TLRs has not been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Cell death has a crucial role in aspects of immune responses against pathogen infection. Pyroptosis, a type of regulated cell death, controls microbial survival and contributes to the regulation of the host immune response (37)(38)(39). Recent studies of the role of pyroptosis in Kp infection have suggested that Kp-induced pyroptosis is important for the development of host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death has a crucial role in aspects of immune responses against pathogen infection. Pyroptosis, a type of regulated cell death, controls microbial survival and contributes to the regulation of the host immune response (37)(38)(39). Recent studies of the role of pyroptosis in Kp infection have suggested that Kp-induced pyroptosis is important for the development of host immunity.…”
Section: Discussionmentioning
confidence: 99%